Descriptive Epidemiology of Female Suicides by Race and Ethnicity. - Price, James H.; Foh, Erica Payton (Journal of Community Health, 2024)
Each year millions of females develop serious mental illnesses (SMI), which are major risk factors for suicides. Using the Web-Based Injury Statistics Query and Reporting System (WISQARS) for the years 2000, 2010 and 2020, we found in 2020 9,428 females (almost 190/week) committed suicide, losing 328,653 years off potential life before age 80 years. There were pronounced increases in female suicides from 2000 to 2020 across all racial and ethnic groups. The greatest number of suicides were in non-Hispanic white females, but the highest rate of suicides was in non-Hispanic American Indians /Alaska Natives, and in females 15–24 years of age. The West had the highest female suicide rates, with methods used to commit suicides varying by census regions and race and ethnicity. Suffocation to commit suicide increased for most racial and ethnic groups and poisonings decreased for most groups between 2000 and 2020, These underscore the need for targeted primary prevention of suicides for females based on age, geographic location and method of suicide, to mitigate female suicides improved access (e.g. geographically and financially) to mental health care services is essential.